Motivation thru Experience - Vyas, Amit (Social Science Learning Education Journal, 2017)
âWhen I was in kindergartenstandard, my mother always told me that happiness is the key to life. When I went to school, they asked me what I want to be when I grew upâ. I wrote down âhappyâ. The school managementconcluded that I didnât understand their assignment. But I told them that they didnât understand life. I havenât met anyone yet who has not felt the sting of rejection at some point in his/her life. One has probably been rejected by friends or family or teacher or hisjob application was turned down. One has to understand that being rejected is not a bad thing. Itâs your attitude - when youare rejected that matters. Donât we want to prove people wrong - when we get rejected?